Cardiovascular drug use among people with cognitive impairment living in nursing homes in northern Sweden - Svahn, Sofia; Lövheim, Hugo; Isaksson, Ulf; Sandman, Per-Olof; Gustafsson, Maria (European Journal of Clinical Pharmacology, 2020)
Purpose: The aim of this study was to describe changes in the pattern of cardiovascular agents used in elderly people living in nursing homes between 2007 and 2013. Further, the aim was to analyse the use of cardiovascular drugs in relation to cognitive impairment and associated factors within the same population, where prescription of loop diuretics was used as a proxy for heart failure. Methods: Two questionnaire surveys were performed including 2494 people in 2007 and 1654 people in 2013 living in nursing homes in northern Sweden. Data were collected concerning drug use, functioning in activities of daily living (ADL) and cognition, using the Multi-Dimensional Dementia Assessment Scale (MDDAS). The use of different drugs and drug classes among people at four different levels of cognitive function in 2007 and 2013 were compared. Results: The proportion of people prescribed ASA and diuretics was significantly lower at all four levels of cognitive function in 2013 compared to 2007. Among people prescribed loop diuretics, the use of angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers (ACEI/ARBs) increased from 37.8 to 45.6%, β-blockers from 36.0 to 41.8% and warfarin from 4.4 to 11.4%. The use of warfarin, ACEI/ARBs, β-blockers and mineralocorticoid receptor antagonists (MRAs) were less common among individuals with more severe cognitive impairment. Conclusion: The results indicate that cardiovascular drug treatment has improved between 2007 and 2013, but there is room for further improvement, especially regarding adherence to guidelines for heart failure. Increasing cognitive impairment had an effect on treatment patterns for heart failure and atrial fibrillation.